Spatio-temporal impact assessment of land use / land cover (LU-LC) change on land surface temperatures over Jaipur city in India - Neha Gupta; Aneesh Mathew; Sumit Khandelwal (International Journal of Urban Sustainable Development, 2020)
Urban development has consequently given rise to the empirically observed phenomenon of the urban heat island (UHI). The article aims to determine the change in land surface temperature (LST) over Jaipur study area during the period from 2008 to 2011 and analyzes the spatial variation of LST in the context of changes in land use/land cover (LU-LC). The LST has been retrieved from Moderate Resolution Imaging Spectroradiometer (MODIS) images for the years 2008 and 2011 to find the variation of LST as per the LU-LC classes. Results show a significant rise in temperature for all LU-LC categories during the study period. The percentage impervious surface area (ISA) pattern of these classes has also been analyzed for both the years, and a rising trend in ISA for different LU-LC categories has been observed; showing that Jaipur city has witnessed substantial growth in built-up area at the cost of greener patches and open land at a fast pace having a clear impact on LST variation. The average rise in temperature during winter season was found to be around 2.6 °C while 1.47 °C rise was observed during summers. Inter-seasonal variations of LST on different LU-LC over Jaipur have been analyzed.